Signature pedagogy in theatre arts. (July 2017) - Kornetsky, Lisa
Critique in undergraduate theatre programs is at the heart of training actors at all levels. It is accepted as the signature pedagogy and is practiced in multiple ways. This essay defines critique and presents the case for why it is used as the single most important way that performers come to understand the language, values, and discourse of the discipline. In actor training, critique is used in the studio, classroom, and rehearsal hall as the way that students learn to take theory and practical skills and apply them through choices that are clear and justifiable, demonstrating an understanding of text and dramatic style. The focus is on where and how critique is used, who is doing the critique in what setting, and how students learn and grow through this process. This is discussed in relationship to the development of self and community and preparation for the professional world.